THE EFFECT OF IMPLEMENTING THE PBL MODEL TOWARDS CRITICAL THINKING ABILITIES IN THE KURIKULUM MERDEKA FOR ELEMENTARY SCHOOL STUDENTS - Prihantini, Prihantini; Murthada, Murthada; Saepuloh, Aep; Amahoru, Archristhea; Ahyani, Edi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Problem Based Learning is learning that focuses on the learning that students do and everything that students do to receive knowledge. In learning with the PBL model, students are expected to have real problems to solve. The main objective of this study is to assess the impact of implementing the PBL approach on the development of critical thinking abilities among elementary school students following the Kurikulum Merdeka. This study falls under the category of experimental research and employs Simple Random Sampling as the sampling technique. The primary research instrument utilized in this study is a test designed to evaluate student learning outcomes, while the t-test is employed as the data analysis technique. The findings of this research reveal that the average score obtained by the experimental group is 81.32, whereas the control group scores an average of 72.2. Consequently, it can be deduced from the research findings that the utilization of the PBL model significantly enhances students' critical thinking skills. As a result, it is highly recommended that teachers incorporate the PBL model into their instructional practices.